IMMU-29. AIF1 IS A PROGNOSTIC BIOMARKER AND CORRELATED WITH IMMUNE INFILTRATES IN GLIOMAS. (4th December 2020) - Chai, Yi; Liu, Wei; Wang, Junhua; Hu, Libo; Zhang, Yuqi
Abstract: Gliomas remain highly variable clinical behaviors, leading to emerging studies to identify prognostic factors. AIF1 (Allograft Inflammatory Factor 1) is critical for promoting both macrophage- and dendritic cells (DCs)-mediated inflammatory response and growth of vascular smooth muscle cells and T-lymphocytes. Through comparative analyses of primary LGG patients from The Cancer Genome Atlas (TCGA) dataset and Chinese Glioma Genome Atlas(CGGA) dataset, we reported that the expression level and methylation level of AIF1 gene vary among glioma patients and AIF1 expression or gene body methylation is significantly associated with glioma patient survival. Cox regression results confirmed that AIF1 played an independent predictor of survival in lower-grade glioma(LGG), with a cox coefficient of 0.251 indicating a worse prognosis. Moreover, AIF1 expression was positively correlated with infiltrating levels of CD4+ T and B cells, macrophages, neutrophils, and DCs in LGG and glioblastoma(GBM). AIF1 expression also showed strong correlations with specific immune cell markers in LGG and GBM. In addition, AIF1 expression potentially contributed to the regulation of glioma-associated macrophages and microglia. In conclusion, our findings suggested that AIF1 was correlated with prognosis and immune infiltrating levels, and it can be used as a prognostic factor in gliomas.